Modulation of TRPA1 channel activity by Cdk5 in sensory neurons. Issue 1 (1st January 2018) - Sulak, Michael A.; Ghosh, Monica; Sinharoy, Pritam; Andrei, Spencer R.; Damron, Derek S.
ABSTRACT: Transient receptor potential cation channel, subfamily A, member 1 (TRPA1), is activated by a broad range of noxious stimuli. Cdk5, a member of the Cdk family, has recently been identified as a modulator of pain signaling pathways. In the current study, we investigated the extent to which Cdk5 modulates TRPA1 activity. Cdk5 inhibition was found to attenuate TRPA1 response to agonist in mouse DRG sensory neurons. Additionally, the presence of active Cdk5 was associated with increased TRPA1 phosphorylation in transfected HEK293 cells that was roscovitine-sensitive and absent in the mouse mutant S449A full-length channel. Immunopurified Cdk5 was observed to phosphorylate human TRPA1 peptide substrate at S448A in vitro . Our results point to a role for Cdk5 in modulating TRPA1 activity.